(untitled) (Revista Brasileira Multidisciplinar, 2009)
The nitrite and nitrate salts in excess are harmful to health. This work aimed at evaluating the quality of the Tuscan sausages from several producers, commercialized in the region of Franca-SP, Brazil, through the analytic quantitative method of spectrophotometry. In parallel, an evaluation of the level of knowledge of the region’s producers about the risks of the abusive use of the additive was done. The nitrite levels were analyzed in six samples of Tuscan sausage, numerically classified as: I, II, II, IV, V and VI, collected in different supermarkets. The method was based on the nitrite reaction with sulphanilic acid and -naphthol with formation of a colored compound. It was verified that the samples I, II and III presented a higher nitrite concentration than the one allowed by legislation (150 mg/kg). The questionnaire applied to three of the six producers, revealed that two of them did not know the legislation, did not do nitrite concentration analysis and only one declared that he did not know the harm that this additive could cause if indiscriminately used. The results showed that 50% of the samples were in disagreement with the legislation, thus, preventive measures must be taken such as quality control for industries and health monitoring of the food involved.